Creatine supplementation and health variables: a retrospective study - Schilling, B. K.; Stone, M. H.; Utter, A.; Kearney, J. T.; Johnson, M.; Coglianese, R.; Smith, L.; O'Bryant, H. S.; Fry, A. C.; Starks, M.; Keith, R.; Stone, M. E. (Medicine & Science in Sports & Exercise, 2001)
Purpose: Long-term safety of creatine supplementation has been questioned. This retrospective study was performed to examine markers related to health, the incidence of reported side effects and the perceived training benefits in athletes supplementing with creatine monohydrate. Methods: Twenty-six athletes (18 M and 8 F, 24.7 +/- 9.2 y; 82.4 +/- 20.0 kg; 176.5 +/- 8.8 cm) from various sports were used as subjects. Blood was collected between 7:00 and 8:30 a.m. after a 12-h fast. Standard clinical examination was performed for CBC and 27 blood chemistries. Testosterone, cortisol, and growth hormone were analyzed using an ELISA. Subjects answered a questionnaire on dietary habits, creatine supplementation, medical history, training history, and perceived effects of supplementation. Body mass was measured using a medical scale, body composition was estimated using skinfolds, and resting heart rate and blood pressure were recorded. Subjects were grouped by supplementation length or no use: Gp1 (control) = no use (N = 7; 3 F, 4 M); Gp2 = 0.8-1.0 yr (N = 9; 2 F, 7 M); and Gp3 = 1+ (N = 10; 3 F, 7 M). Results: Creatine supplementation ranged from 0.8-4 yr. Mean loading dose for Gp2 and Gp3 was 13.7 +/- 10.0 and the maintenance dose was 9.7 +/- 5.7 g.d-1. Group differences were analyzed using one-way ANOVA. Conclusions: Expected gender differences were observed. Of the comparisons made among supplementation groups, only two differences for creatinine and total protein (P < 0.05) were noted. All group means fell within normal clinical ranges. There were no differences in the reported incidence of muscle injury, cramps, or other side effects. These data suggest that long-term creatine supplementation does not result in adverse health effects.